Fibroblast growth factor 21 analogue LY2405319 lowers blood glucose in streptozotocin‐induced insulin‐deficient diabetic mice by restoring brown adipose tissue function. Issue 2 (28th November 2014) - Kim, J.‐H.; Bae, K.‐H.; Choi, Y.‐K.; Go, Y.; Choe, M.; Jeon, Y.‐H.; Lee, H.‐W.; Koo, S.‐H.; Perfield, J. W.; Harris, R. A.; Lee, I.‐K.; Park, K.‐G.
<x xml:space="preserve">Abstract</x> Aim To investigate the effects of LY2405319, an analogue of fibroblast growth factor 21 (FGF21), on glucose homeostasis in streptozotocin (STZ)‐induced insulin‐deficient mice (STZ mice). Methods Nine‐week‐old male C57BL/6J mice were administered a single intraperitoneal injection of STZ (150 mg/kg). One week later, after confirmation of hyperglycaemia, saline or LY2405319 (5 mg/kg) was injected subcutaneously daily for 4 weeks. Changes in glucose homeostasis, energy metabolism and brown adipose tissue (BAT) function were assessed. Results The STZ mice had elevated blood glucose and reduced plasma FGF21 levels, impaired glucose uptake in the BAT, and BAT mitochondria with absent or swollen cristae and fewer lipid vacuoles. LY2405319 significantly reduced blood glucose levels and this was associated with increased BAT glucose uptake and changes in gene expression and morphology, indicating improved mitochondrial lipid metabolism in the BAT. Importantly, the ability of LY2405319 to lower blood glucose in STZ mice was compromised after removing interscapular BAT. Conclusions Our results show that LY2405319 reduces blood glucose levels in insulin‐deficient diabetes by improving BAT metabolism. Additional studies investigating the therapeutic potential of FGF21 for the treatment of type 1 diabetes are warranted.